2009
DOI: 10.2503/jjshs1.78.218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cutting Time and Low-temperature Treatment of Rooted Cuttings on Stem Elongation and Leaf Number in Cultivars of Chrysanthemum morifolium Ramat.

Abstract: The effects of cutting time and low-temperature treatment of rooted cuttings on stem length and leaf number after planting were investigated in ten Chrysanthemum cultivars. Rooted cuttings propagated from mother plants on three different dates (September 30, November 10, and December 14) were planted two weeks after cutting and grown at constant temperatures of 20°C (7:00-19:00) and 12.5°C (19:00-7:00) under long days. In addition, rooted cuttings treated at 2.5°C for six weeks were planted on October 14 and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The ILN of cuttings from mother plants grown at 7°C or 10°C was significantly decreased compared with that of plants grown at 13°C or 16°C, and there was no significant difference between ILN in the 7°C and 10°C treatments. It is well known that 'Shuho no Chikara' has a strong rosette habit (Ohishi et al, 1986;Tanigawa et al, 2009). Konishi (1975) reported that 'Okayamaheiwa' plants treated with low temperature for a shorter period formed rosettes, whereas those treated for a longer period underwent stem elongation and flowered rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…The ILN of cuttings from mother plants grown at 7°C or 10°C was significantly decreased compared with that of plants grown at 13°C or 16°C, and there was no significant difference between ILN in the 7°C and 10°C treatments. It is well known that 'Shuho no Chikara' has a strong rosette habit (Ohishi et al, 1986;Tanigawa et al, 2009). Konishi (1975) reported that 'Okayamaheiwa' plants treated with low temperature for a shorter period formed rosettes, whereas those treated for a longer period underwent stem elongation and flowered rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…forms a rosette or rosette-type growth form in autumn and winter (Cathey, 1954;Konishi, 1975;Mason and Vince, 1958;Okada, 1959Okada, , 1963Tanigawa et al, 2009). After passing through the rosette stage, the plants grow rapidly and flower early in a heated greenhouse at temperatures of 15-20°C (Cathey, 1954;Schwabe, 1950).…”
Section: Introductionmentioning
confidence: 99%